The Bialskie Mts. (Eastern Sudetes, Poland), an extraordinary bryological area - Wierzcholska, Sylwia; Plášek, Vítězslav (Biodiversity: Research and Conservation, 2006)
The results of the bryological investigations carried out in the years 2001-2005 in The Bialskie Mts. (E Sudetes, SW Poland) are presented by the authors. A total of 170 species of mosses have been recorded there. Comments about 34 threatened, rare, and most interesting species are given. The moss flora of the study area is briefly assessed and the ecological moss groups, e.g. terricolous, epiphytic, epixylous, coprophilous and others, are characterized in detail.